Quantization of Space-Time I-Party - Lawler, James H.L. (1998)
In this work there are seven new majar or key concepts including postulate that space-time itself is quantized. Based upon these new concepts it is possible to deduce more than forty new sub concepts. These provide a simpler, but more detailed and precise explanation of our Universe than has been possible befare. In this way so me phenomena which were believed quite independent of one another are explained with deeper connection being shown between them. The seven key concepts postulated here are: (1) The Concept of lrrelevance (Lawler [ 1 39]), (2) A Photon Model, (3) The Photonic Composition of all Particles, (4 )The Quantization of Space-Time into Spasons, (S)The lnterdependence of Space and Time, Time is Change, (6) lndexing, The ldentification Units or Quanta of Spasons, and (7) The Theory of Everything (TOE):Everything in the Universe is lnterdependant.